Control of Phytophthora cinnamomi in Erica sessiliflora and Erica davisii - Casonato, S.G.; Manning, M.A.; Rheinlander, P.A.; Fullerton, R.A. (New Zealand Plant Protection, 2008)
A field trial was conducted to test the efficacy of two fungicides (metalaxyl and phosphorous acid) and supplementary organic matter for the control of Phytophthora cinnamomi root rot in Erica sessiliflora and E davisii Five treatments were applied (1) untreated control (2) metalaxyl (3) phosphorous acid (4) metalaxyl plus phosphorous acid and (5) organic soil amendment Plants were assessed for plant health as an indication of possible P cinnamomi infection Phosphorous acid applied alone or in combination with metalaxyl resulted in a significant reduction in the number of diseased or dead E sessiliflora plants compared with the untreated control plants (P0011 and P0004 respectively) The mean health index of phosphorous acid treated E davisii plants was not different (P>005) to control plants Results suggest that this species of Erica has some tolerance to P cinnamomi Metalaxyl applications alone or organic matter treatments did not reduce disease relative to controls in either species